2018
DOI: 10.1016/j.beth.2017.07.007
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy and Acceptability of Third-Wave Behavioral and Cognitive eHealth Treatments: A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: eHealth is an innovative method of delivering therapeutic content with the potential to improve access to third-wave behaviural and cognitive therapies. This systematic review and meta-analysis aimed to determine the efficacy and acceptability of third-wave eHealth treatments in improving mental health outcomes. A comprehensive search of electronic bibliographic databases including PubMed, PsycINFO, Web of Science, and CENTRAL was conducted to identify randomized controlled trials of third-wave treatments in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
35
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 83 publications
6
35
1
Order By: Relevance
“…It is anticipated that this will be completed within a 2-year period, with approximately 70% of participants retained (30% attrition). This is in line with similar eHealth studies where one meta-analysis reported a 23% dropout overall for eHealth interventions57 and another which reported a weighted average attrition of 35% for online interventions 71. For ACT-specific studies, longer, intensive online interventions (eg, 45 min each session, 6 sessions) have reported a 45% attrition,33 while shorter ACT online studies (eg, 15 min per session, 3 sessions) have reported as little as 8% attrition 31.…”
Section: Methodssupporting
confidence: 91%
See 2 more Smart Citations
“…It is anticipated that this will be completed within a 2-year period, with approximately 70% of participants retained (30% attrition). This is in line with similar eHealth studies where one meta-analysis reported a 23% dropout overall for eHealth interventions57 and another which reported a weighted average attrition of 35% for online interventions 71. For ACT-specific studies, longer, intensive online interventions (eg, 45 min each session, 6 sessions) have reported a 45% attrition,33 while shorter ACT online studies (eg, 15 min per session, 3 sessions) have reported as little as 8% attrition 31.…”
Section: Methodssupporting
confidence: 91%
“…We also assumed an attrition rate of 30% (ACT intervention and waitlist control) and separated by three time periods (see figure 1). The attrition rates predicted are in line with reported rates in similar eHealth studies57 71 (see the Feasibility section for more details). From this sample, we intend to recruit at least 15 participants in at least three focus groups (5 in each group) to determine the acceptability of the intervention itself and the feasibility of the pilot trial design.…”
Section: Methodssupporting
confidence: 85%
See 1 more Smart Citation
“…97 Both acceptance and commitment therapy and mindfulness-based interventions have also shown promise in the treatment of anxiety and depression, with evidence that either is more efficacious than waitlist conditions and at least as efficacious as other well-validated psychotherapeutic interventions (e.g., cognitive behavioural therapy). [98][99][100][101] Finally, data from a randomised controlled effectiveness trial comparing Unstuck and On Target (a cognitive behavioural intervention) versus social skills intervention highlighted improvements in flexibility, rule-following, ability to make transitions, problem-solving, and planning/organisation skills among school-age children with autism spectrum disorders. 84 To date, neither acceptance and commitment therapy nor Unstuck and On Target have not been tested in children/adolescents with CHD.…”
Section: Psychotherapeutic Treatment Of Inflexibilitymentioning
confidence: 99%
“…Support for the effectiveness of ACT has been established for a wide range of psychological problems as well as for improving mental health ( A-Tjak et al, 2015 ; French et al, 2017 ; Ruiz, 2012 ). In addition, some meta-analyses on Internet-based third-wave mindfulness and acceptance treatments have shown to be effective in improving wellbeing and mental health outcomes including depression, anxiety, and stress, among others ( Brown et al, 2016 ; O'Connor et al, 2017 ; Spijkerman et al, 2016 ). ACT-based Internet interventions targeting the university student population, which is the focus of this paper, have also been shown to be effective in enhancing wellbeing and alleviating the effects of most common psychological problems experienced by students ( Hunt and Eisenberg, 2010 ), such as stress, anxiety, and depression ( Levin et al, 2017 ; Levin et al, 2016 ; Räsänen et al, 2016 ; Viskovich and Pakenham, 2018 ).…”
Section: Introductionmentioning
confidence: 99%